ZrN coatings on U8 steel obtained by electrospark alloying after a concentrated solar irradiation - Paustovsky, A.V.; Pasichny, V.V.; Novikova, V.I.; Mordovets, N.M.; Isaeva, L.P.; Ostapenko, S.A. (Functional Materials, 2008)
Structure, hardness, and tribological characteristics of electrospark coatings from ZrN-(Cr, Ni, Al₂O₃) on US steel after treatment by concentrated solar radiation (CSR) have been investigated. It is shown that the intensity of wear and factor of friction of specimens with coating after CSR are essentially less than for non-treated US steel. At changing of regime of CSR treatment from 785°C, 25.3 s to 530°C, 8.6 s and at decreasing of sliding speed at wear test from 10 m/s to 5 m/s the tribological characteristics improves. After treatment by CSR the strengthening of steel surface is observed the quenching with formation of martensite and troostite take place. At treatment by concentrated solar radiation changing in phase composition of coatings observed: before treatment by CSR the main phase in coating is ZrO₂ (cubic), after treatment by CSR the main phase is ZrNi, ZrO₂ (tetragonal) is also present. Вивчено структуру, твердість, трибологічні характеристики електроіскрових покриттів з ZrN-(Cr, Ni, Al₂O₃) на сталі У8 після обробки концентрованим сонячним випромінюванням (КСВ). Показано, що інтенсивність зношування та коефіцієнт тертя зразків з покриттям після впливу КСВ суттєво менше, ніж необробленої сталі У8. При зміненні режиму обробки КСВ від 785°С, 25,3 с до 530°С, 8,6 с та при зменшенні швидкості ковзання при випробуванні на тертя від 10 м/с до 5 м/с трибологічні характеристики покращуються. Після обробки КСВ спостерігається зміцнення поверхні сталі має місце загартування з утворенням мартенситу та трооститу. При обробці концентрованим сонячним випромінюванням спостерігаються змінення у фазовому складі покриттів: до обробки КСВ основна фаза у покритті ZrO₂ (кубічний), після обробки КСВ основна фаза ZrNi, присутній також ZrO₂ (тетрагональний). Исследованы структура, твердость, трибологические характеристики электроискровых покрытий из ZrN-(Cr, Ni, Al₂O₃) на стали У8 после обработки концентрированным солнечным излучением (КСИ). Показано, что интенсивность износа и коэффициент трения образцов с покрытием после воздействия КСИ существенно меньше, чем необработанной стали 'У8. При изменении режима обработки КСИ от 785°С, 25,3 с до 530°С, 8,6 с и при уменьшении скорости скольжения при испытании на трение от 10 м/с до 5 м/с трибологические характеристики улучшаются. После обработки КСИ наблюдается упрочнение поверхности стали происходит закалка с образованием мартенсита и троостита. При обработке концентрированным солнечным излучением наблюдаются изменения в фазовом составе покрытий: до обработки КСИ основная фаза в покрытии ZrO₂ (кубический), после обработки КСИ основная фаза ZrNi, присутствует также ZrO₂ (тетрагональный).